Primordial Germ Cells Quality of Chicken Embryo from Post Cryopreservation Blood Samples - Azizah, Nurul; Kostaman, Tatan; Tribudi, Yuli Arif; Kusumaningrum, Diana Andrianita; Suyatno, Suyatno; Muttaqin, Zultinur; Koswara, Eko; Gunawan, Muhammad (Jurnal Medik Veteriner, 2024)
The optimal cellular reservoir for the conservation and propagation of endangered poultry is acknowledged to be primordial germ cells (PGCs). This study aimed to evaluate and compare the efficacy of cryopreserving PGCs derived from purified sources and blood samples. The experimental design encompassed two treatment groups, each iterated six replication. Blood samples that had been filled with 500 µL of phosphate-buffered saline without Ca2+ and Mg2+ (PBS) underwent centrifugation at 1200 rpm for six minutes. The supernatant was discarded and the pellet was mixed with 500 µL 10% FBS-PBS and was then subdivided for cryopreservation and PGCs purification. Cryopreservation included the controlled freezing of blood and purified PGCs samples in Nalgene cryogenic vials with the incorporation of banker cells. Following thawing, statistical analyses revealed no significant variance in the mean PGCs count between purified PGCs and blood samples (p > 0.05). The percentages of PGCs mortality and the recovery rate demonstrated statistical significance (p < 0.05). Further investigations indicated that cryopreserving blood samples significantly increased the recovery rate of PGCs while decreasing post-thaw mortality. Morphology of PGCs from blood cryopreservation showed similar morphology to PGCs in general. The potential application of cell-based cryo-banking will contribute to the preservation of poultry genetic diversity for sustainability and adaptation to future poultry demands.